Investigation of the versatility of SPES membranes customized with sulfonated molybdenum disulfide nanosheets for DMFC applications. (8th June 2020) - Divya, Kumar; Rana, Dipak; Sri Abirami Saraswathi, Meenakshi Sundaram; Bhat, Santoshkumar D.; Shukla, Avanish; Nagendran, Alagumalai
Abstract: Sulfonated poly(ether sulfone) (SPES) based proton exchange membranes (PEMs) are fabricated using sulfonated molybdenum disulfide (S-MoS2 ) nanosheets via facile solution casting method. SPES (DS = 30%) and S-MoS2 are synthesized and sulfonation is evidently observed in FTIR and XRD analysis. The anchoring of sulfonic acid group on exfoliated molybdenum disulfide (E-MoS2 ) and elemental composition of S-MoS2 are confirmed by XPS spectrum. Physico-chemical characteristics such as ion-exchange capacity (IEC), water uptake, swelling ratio and oxidation stability are found to be increases after the addition of S-MoS2 into SPES matrix. Increment in S-MoS2 content in SPES matrix decreases the surface contact angle due to the increase in hydrophilicity. Further, the dispersing ability of S-MoS2 in SPES matrix is evidently shown by an increase in surface roughness, tensile strength and thermal stability of the SPES/S-MoS2 nanocomposite membranes. On the whole, SPES/S-MoS2 -1 membrane showed the highest proton conductivity of 5.98 × 10 −3 Scm −1, selectivity of 19.6 × 10 4 Scm −3 s, peak power density of 28.28 mWcm −2 and lesser methanol permeability of 3.05 × 10 −8 cm 2 s −1 . The strong interfacial interaction between SPES and S-MoS2 in nanocomposite membranes create strong hydrogen bond network to facilitate the proton conduction pathway via both vehicle and Grotthuss type mechanisms. Overall results suggested that the SPES/S-MoS2 nanocomposite membranes are superior and appropriate alternative for commercially high-cost Nafion® membranes for use in renewable direct methanol fuel cell (DMFC) devices. Graphical abstract: Image 1 Highlights: Superior and low-cost SPES PEMs were fabricated using S-MoS2 as nano-additive. SPES/S-MoS2 -1 PEM showed better proton conductivity of 5.98 × 10 −3 Scm −1 and membrane selectivity of 19.6 × 10 4 Scm −3 s. SPES/S-MoS2 -1 PEM exhibited a higher power density of 28.28 mWcm −2 and lesser methanol permeability of 3.05 × 10 −8 cm 2 s −1 . SPES/S-MoS2 PEMs found to be an alternate for expensive Nafion in DMFCs.